Immigrants to Canada, by province or territory of destination - Statistics Canada (Government of Canada, 2017)
This table contains 15 series, with data for years 1946 - 2004 (not all combinations necessarily have data for all years). This table contains data described by the following dimensions (Not all combinations are available): Geography (15 items: Canada; Prince Edward Island; Nova Scotia; Newfoundland and Labrador ...).